Some Current Advanced Researches on Information and Computer Science in Vietnam Post-proceedings of The First NAFOSTED Conference on Information and Computer Science - Dang, Q.A (Springer, 2015)
This book includes the extended and revised versions of a set of selected papers from the First NAFOSTED Conference on Information and Computer Science (NICS’2014), held at Le Quy Don Technical Academy, Hanoi, Vietnam from 13/Mar./2014 to 14/Mar./2014. The conference was co-organized by The National Foundation for Science and Technology Development (NAFOSTED) and Le Quy Don Technical Academy. The purpose of the NICS conference series is to promote scientific publications in the country and to provide a platform for high quality academic exchange among scientists in the fields of computer science, information and communication. The conference includes five tracks, namely “Computer Science”, “Artificial Intelligence”, “Network Systems”, “Software Engineering”, and “Information Systems”. The papers in this book are among the best contributions at NICS’2014 taken into account the quality of their presentation at the conference and the recommendation of the two experts in the extra round of independent review.